Recovery rhetoric: a critical discourse analysis of substance use recovery. - McNeil, Sandra R. (Critical Discourse Studies, 2023)
Dominant discourses of recovery permeate substance use research, policy, and practice recommendations around the world, exercising the power to shape the identities of people with substance use issues. Drawing on Foucauldian and intersectionality theories, this study explores power operations embedded in recovery discourses constructing a certain type of recovery for a certain type of subject. A critical discourse analysis using van Leeuwen's social semiotic approach examines two Canadian federal recovery documents to consider the discursive representation of people with substance use issues, legitimization of recovery, and interpretation of space. Findings suggest that substance use recovery discourses are entwined in a complex web of neoliberal, biomedical, and moral discourses by which stigmatized identities are (co)constructed at micro, mezzo, and macro levels. This study offers a unique and relevant opportunity to complicate the dominant recovery literature by challenging oppression, deconstructing normative identities, and facilitating the empowerment of marginalized populations.